Actualización del test de proyecciones de cuatro minutos en judocas femeninas de la preselección nacional - Fernández, R.; Pujadas, A.; Pérez, P. (Revista Cubana de medicina del deporte y la cultura fisica, 2018)
The changes recently introduced in the regulations, by increasing the fighting dynamics and their physiological demands have modified the preparation of judokas. For this reason, evaluative studies exactly adjusted to the competitive requirements are required. As a result, Sports Medicine physicians in join with coaches have introduced a Four Minutes Projection Test. Its protocol was 3 pending validation and therefore it was not known if it could provide the information needed to assess the special resistance in high-level judokas. This research studies the results of test application to the first seven athletes of the Cuban National Pre-selection, in tree times, during their preparation for the 2016 Olympic Games. Heart rate and blood lactate concentration were measured in both resting and post-loading conditions, in addition to performance variables. The information was processed in the version 22 of SPSS-W statistical package and the Wilcoxon test for pre and post test results and the Kruskal Wallis test for differences among weight groups were used as statistical tests. It was possible to determine the high quality of the performance, as well as of the cardiovascular and metabolic responses to the effort made, in the total of the sample, according to preparation stage. There were demonstrated the usefulness of the test to diagnose the special resistance in female elite judokas and the attributes of the test used.